2017
DOI: 10.1155/2017/3432074
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Gait Analysis to Study Stress Distribution of the Human Foot

Abstract: Researchers and clinicians are increasingly using plantar pressure and force measurement system to evaluate foot functions. This research evaluates the quality and reliability of a Tekscan HR mat to study the plantar pressures and forces acting during walking, running, jumping, and standing of healthy subjects. The following regions of the foot were investigated: heel, mid foot, metatarsophalangeal joint, hallux, and the toes. The arches of both feet of the three healthy subjects in the gait analysis were pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 31 publications
1
16
0
1
Order By: Relevance
“…This is the rst study to evaluate and access temporo-spatial and kinetic data for rhesus monkeys using a pressure-sensing walkway system. This sensor system has been widely applied to the gait study of very small to large animals and has also used in clinical human studies, because it provides automated calculation of gait parameters without additional technical equipment, such as markers on the skin and calibrated camera setups (21)(22)(23). Our results showed that there were no signi cant differences between temporo-spatial and kinetic gait parameter values, but there were detectable right-left symmetries between the limbs on the opposite side.…”
Section: Discussionmentioning
confidence: 72%
“…This is the rst study to evaluate and access temporo-spatial and kinetic data for rhesus monkeys using a pressure-sensing walkway system. This sensor system has been widely applied to the gait study of very small to large animals and has also used in clinical human studies, because it provides automated calculation of gait parameters without additional technical equipment, such as markers on the skin and calibrated camera setups (21)(22)(23). Our results showed that there were no signi cant differences between temporo-spatial and kinetic gait parameter values, but there were detectable right-left symmetries between the limbs on the opposite side.…”
Section: Discussionmentioning
confidence: 72%
“…The shoe hygienic insoles, which are 2 mm thick, were equipped with seven force-sensing resistors (FSR400, Interlink Electronics, Inc., CA). The sensors respond to stimulation ranging from 0.2-20 N (8.13-813 kPa), allowing the measurement of human peak plantar pressure (Nandikolla et al, 2017). The sensors were placed on the heel, lateral midfoot, center of the midfoot, lateral forefoot, center of the forefoot, medial forefoot, and big toe ( Fig.…”
Section: -Sensor Plantar Pressure Measurement Insolementioning
confidence: 99%
“…Severe varus feet had greater total pressure in the lateral midfoot and lateral forefoot, and decreased pressure in the medial forefoot [15]. They also had decreased and delayed initial peak forces of the hallux [22,26,28] while the first metatarsophalangeal joint displayed higher pressure compared to normal feet [29]. Dynamic pedobarography was able to detect an improvement in peak plantar pressure patterns, pressure-time integrals, and contact area in post-operative surgical correction of cavovarus deformity.…”
Section: Normal Feetmentioning
confidence: 99%